A sociedade literária de Belo Horizonte: um legado cultural da Biblioteca Municipal para a cidade - Aline Pinheiro Brettas (2004)
The main purpose of the present work is to reconstruct the history of the Belo Horizonte Public Library, since its foundation until its extinction. Further to that, we have analyzed its contribution for the memory and the identity of the city. First of all, well present the justification for the present work, as well as some considerations about its methodology and its theoretical reference. The theoretical reference was based in studies regarding the Public Library. As for the methodology, it had, as its main aspect, the documental analysis, complemented by researches and theoretical sources. The documents which have been analyzed have official origin such as reports and the legislation, as well, as unofficial ones, such as newspapers articles. These documents have made it possible a contraposition related to favourable and unfavourable opinions about the Library. The favourable opinions are usually provided by the Municipal Administration and the Library Direction. The unfavourable opinions were provided by those who used to visit the institution, and were informed throught newspapers and magazines. This contraposition permitted a dialectical approach. The story of the Library was divided into creation, trajectory administrative, technical, political, ideological and socio-cultural aspects - and the extinction of the institution. The contribution of the Belo Horizonte Public Library for the constitution of the memory and identity of the city is proved. It happened in a positive manner, through the heap and the services offered by the institution.